2014
DOI: 10.1007/s12026-014-8544-x
|View full text |Cite
|
Sign up to set email alerts
|

NLR proteins and parasitic disease

Abstract: Parasitic diseases are a serious global health concern. Many of the most common and most severe parasitic diseases, including Chagas’ disease, leishmaniasis, and schistosomiasis, are also classified as neglected tropical diseases and are comparatively less studied than infectious diseases prevalent in high income nations. The NLRs (nucleotide-binding domain leucine-rich-repeat-containing proteins) are cytosolic proteins known to be involved in pathogen detection and host response. The role of NLRs in the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 97 publications
(102 reference statements)
4
50
0
1
Order By: Relevance
“…However, an approximately threefold increase in the anion transporter B3AT, an AD and senescence marker was observed. The 2.5‐fold increase in the cytosolic leucine rich repeat LRC59 that binds polyA RNA is also involved in pathogen detection . In sum, most of the proteins in less purified FU‐CJD p18 particles represent host pathologic responses and disease markers.…”
Section: Resultsmentioning
confidence: 99%
“…However, an approximately threefold increase in the anion transporter B3AT, an AD and senescence marker was observed. The 2.5‐fold increase in the cytosolic leucine rich repeat LRC59 that binds polyA RNA is also involved in pathogen detection . In sum, most of the proteins in less purified FU‐CJD p18 particles represent host pathologic responses and disease markers.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have further identified a critical role for the NLRP3 inflammasome in the host response to several viral and parasitic pathogens such as West Nile virus, Dengue virus, Trypanosoma cruzi and malaria (reviewed3233). Importantly, the function and role of the NLRP3 inflammasome was characterized by use of gene-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a wide array of agonists are capable of activating the NLRP3 inflammasome, including those derived from microbes (PAMPs) or from endogenous or environmental sources (DAMPs) (20). Microbial activators of the NLRP3 inflammasome include both Gram-positive and Gram-negative bacteria (Staphylococcus aureus, Listeria monocytogenes, Streptococcus pneumoniae, Neisseria gonorrhoeae, and others) (21), fungi (Candida albicans, Aspergillus fumigatus, Microsporum canis, and others) (22), RNA and DNA viruses (influenza virus, adenovirus, respiratory syncytial virus [RSV], and others) (23), and parasitic pathogens (Plasmodium chabaudi, Leishmania amazonensis, and Schistosoma mansoni) (24). Given the large number of chemically and structurally diverse agonists that are capable of activating the NLRP3 inflammasome, it is unlikely that NLRP3 directly Figure 1.…”
Section: Bacterial Effector Molecules That Facilitate Evasion Of Inflmentioning
confidence: 99%